IDENTIFIKASI PROFIL FITOKIMIA DAN UJI AKTIFITAS ANTIOKSIDAN EKSTRAK DIETIL ETER DAUN SURIAN (Toona sinensis (A.Juss) M.Roem) DENGAN METODE DPPH. - Nurhamidah Nurhamidah; Hazli Nurdin; Yunazar Manjang; Abdi Dharma (ALOTROP, 2019)
Surian Toona sinensis (A.Juss) M. Roem is a plant that is widely used by the community in the field of medicine such as fever, diarrhea, blood booster, tonic and others. This study aims to determine the secondary metabolite compounds found in leaf extracts of Toona sinensis and test the antioxidant activity using the 2,2-diphenyl-1- (2,4,6-trinitrophenyl) -hydrazinyl (DPPH) method. Identification of secondary metabolites by alkaloids, terpenoids, steroids, flavonoids, phenolics, saponins, coumarin and carotenoids. Toona sinensis leaf was extracted using methanol as a solvent. The resulting extract was saponified with a KOH solution in methanol. The saponification results were extracted again with diethyl ether solvent. The ether layer obtained was washed with distilled water, then dried with Na2SO4 and evaporated to dry, then tested its antioxidant activity. The identification results show Surian leaves contain all secondary metabolites except alkaloids. The antioxidant activity parameters of the Surian extract (Toona sinensis) are indicated by the% inhibitory and IC50 values. Test results showed diethyl ether extract had moderate category of antioxidant activity with IC50 122, 3752 ?g / mL